A life cycle assessment comparison of materials for a tidal stream turbine blade. (1st March 2022) - Walker, Stuart R.J.; Thies, Philipp R.
Abstract: Electricity generated from tidal streams via underwater turbines has significantly lower greenhouse gas emissions than fossil-fuel derived electricity. However, tidal stream turbine blades are conventionally manufactured from non-recyclable reinforced polymer composite materials. Tidal stream capacity is forecast to be over 1GW by 2030, which using current methods will ultimately produce around 6000 tonnes of non-recyclable blade waste. This waste is currently disposed of in landfill or incinerated, both of which have greenhouse gas and human health impacts. To address a growing waste management problem, this high-level study considers for the first time a range of conventional and bio-based materials, manufacturing methods, and end-of-life treatments to determine the blade materials and designs likely to have low environmental impact. A finite element model is used to develop material cases and Life Cycle Assessment is used to study the impacts of each over a 'cradle to dock, dock to grave' scope. The impact of material choices on cost and modifications to the wider turbine are considered. Compared to a glass fibre composite turbine blade, steel blades are around 2.5 times heavier, and incur additional environmental impact due to upgrades required to the wider turbine. Carbon fibre composite blades weigh less than glass fibre, but cause greenhouse 80% greater gas emissions, and human and ecosystem health risks, so are also not recommended. The best environmental performance of the cases considered was a flax fibre composite. This material offers greenhouse gas emissions around 50% lower than glass fibre materials when manufactured using conventional epoxy resin, and around 40% lower when manufactured using recyclable epoxy resin, which also enables the reuse of the fibre and may further reduce environmental impact. Initial results suggest that the cost of these materials are similar to or lower than conventional composite materials. Highlights: Turbine blades are often the least recyclable part of a tidal stream turbine. Turbine blades have environmental impact due to materials, manufacture and disposal. Glass fibre blades have low environmental impact vs. carbon fibre or steel blades. Incineration or landfill of composites cause environmental damage and emissions. Bio-based and recyclable solutions have lower impact and potentially lower cost.